2015
DOI: 10.1039/c4cc09928a
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–liquid interface-mediated room-temperature synthesis of amorphous NiCo pompoms from ultrathin nanosheets with high catalytic activity for hydrazine oxidation

Abstract: NixCoy alloy pompoms formed by the aggregation of nano ultrathin sheets were prepared by simultaneous reduction of NiCl2 and CoCl2 with NaBH4via a liquid-liquid interface reaction. Ni1Co3 pompoms produced markedly higher activity and stability as hydrazine oxidation catalysts than Ni, Co and other NixCoy pompom catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…S8a . In acidic electrolyte, the Tafel slopes are 53 and 289 mV dec −1 in the low and high potential regions, respectively, indicating that the mechanism possibly follows the processes of (i) b-Pd@Rh-NCs + NH 2 NH 3 + ↔ b-Pd@Rh‒NHNH 2 + 2 H + + e − and then (ii) b-Pd@Rh‒NHNH 2 → b-Pd@Rh-NCs + N 2 + 3 H + + 3e − , where the rate-determining step is believed to be the first dehydrogenation step (i) based on the comparison of the current and previous literature data 12 , 13 . However, in alkaline solution, much lower Tafel slopes of 15 and 206 mV dec −1 are separately obtained in the low and high potential regions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S8a . In acidic electrolyte, the Tafel slopes are 53 and 289 mV dec −1 in the low and high potential regions, respectively, indicating that the mechanism possibly follows the processes of (i) b-Pd@Rh-NCs + NH 2 NH 3 + ↔ b-Pd@Rh‒NHNH 2 + 2 H + + e − and then (ii) b-Pd@Rh‒NHNH 2 → b-Pd@Rh-NCs + N 2 + 3 H + + 3e − , where the rate-determining step is believed to be the first dehydrogenation step (i) based on the comparison of the current and previous literature data 12 , 13 . However, in alkaline solution, much lower Tafel slopes of 15 and 206 mV dec −1 are separately obtained in the low and high potential regions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…And because of this, if Pt shells are attached to Au, the surface redox properties of the Pt shells are changed, improving stability [431]. For example, Zhang et al [428] reported an Au/Pt/C electrode which displayed no apparent loss of ECSA and only 5 mV degradation of ORR halfwave potential (E 1/2 ) after cycling between 0.6 and 1.1 V (vs. RHE) for 30,000 cycles in HClO 4 (Fig. 25), whereas a Pt/C electrode displayed a 45% ECSA loss and a 39 mV negative shift of ORR E 1/2 .…”
Section: Au As Corementioning
confidence: 99%
“…For example, based on kinetic limitation effects, smooth and near perfect Pt monolayers can be grown in the absence of UPD-type energetic stabilization by using a flow cell setup [296,309]. In another example, Tao et al [312] modified a Cu-UPD process by carefully preparing a UPD solution containing Cu, CuSO 4 and AA to allow the process to be free of potential control, resulting in 1~2 nm Pt nanoclusters being deposited onto Pd nanorods. Adzic et al [289] also performed the Cu-UPD twice to deposit double shells consisting of an outmost monolayer shell of Pt and a monolayer subshell of PdAu onto a Pd core.…”
Section: Principles and Development Of Electrodepositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In alkaline environment, the electrode reaction kinetics has been observed to be higher than those in acid medium, and non‐noble metal catalysts in such medium exhibit better stability . Up to date, a number of non‐noble metals and their alloys for hydrazine oxidation have been investigated, including Co, Cu, Ni and binary and/or ternary Ni‐based metal catalysts (Ni−M, M=Co, Cu, Fe, Zn, B and S) . Among these catalysts reported, the performance of Ni−Zn alloy due to alloying effects stands out as the top level of anode catalysts in DHFCs .…”
Section: Introductionmentioning
confidence: 99%